A systematic review and Meta-data analysis on the applications of Deep Learning in Electrocardiogram - Musa, Nehemiah; Gital, Abdulsalam Ya’u; Aljojo, Nahla; Chiroma, Haruna; Adewole, Kayode S.; Mojeed, Hammed A.; Faruk, Nasir; Abdulkarim, Abubakar; Emmanuel, Ifada; Folawiyo, Yusuf Y.; Ogunmodede, James A.; Oloyede, Abdukareem A.; et al. (Journal of ambient intelligence and humanized computing, 2023)
The success of deep learning over the traditional machine learning techniques in handling artificial intelligence application tasks such as image processing, computer vision, object detection, speech recognition, medical imaging and so on, has made deep learning the buzz word that dominates Artificial Intelligence applications. From the last decade, the applications of deep learning in physiological signals such as electrocardiogram (ECG) have attracted a good number of research. However, previous surveys have not been able to provide a systematic comprehensive review including biometric ECG based systems of the applications of deep learning in ECG with respect to domain of applications. To address this gap, we conducted a systematic literature review on the applications of deep learning in ECG including biometric ECG based systems. The study analyzed systematically, 150 primary studies with evidence of the application of deep learning in ECG. The study shows that the applications of deep learning in ECG have been applied in different domains. We presented a new taxonomy of the domains of application of the deep learning in ECG. The paper also presented discussions on biometric ECG based systems and meta-data analysis of the studies based on the domain, area, task, deep learning models, dataset sources and preprocessing methods. Challenges and potential research opportunities were highlighted to enable novel research. We believe that this study will be useful to both new researchers and expert researchers who are seeking to add knowledge to the already existing body of knowledge in ECG signal processing using deep learning algorithm.